Application of heat-activated peroxydisulfate pre-oxidation for degrading contaminants and mitigating ultrafiltration membrane fouling in the natural surface water treatment. (15th July 2020) - Guo, Yuanqing; Liang, Heng; Bai, Langming; Huang, Kaijie; Xie, Binghan; Xu, Daliang; Wang, Jinlong; Li, Guibai; Tang, Xiaobin
Abstract: Membrane fouling is posing a critical obstacle limiting the widespread application of ultrafiltration (UF). Among the numerous membrane foulants, natural organic matter (NOM) is one of the most problematic since it exists ubiquitously in natural waters and can cause severe membrane fouling. This study investigated the removal of NOM in surface water and the mitigation of membrane fouling using heat-activated peroxydisulfate (PDS) as a pretreatment for UF process. The results demonstrated that the NOM was efficiently removed, with ultraviolet absorbance (UV254 ) and dissolved organic carbon (DOC) decreasing by approximately 71% and 52%, respectively, at a PDS dose of 0.8 mM within 60 min (80 °C). The chromatograms of high performance size exclusion chromatography (HPSEC) indicated that some high molecular weight humic substances with a peak at approximately 10 kDa were oxidized to low molecular weight organic matters distributed in the range of < 100 Da during the pretreatment process. Moreover, three-dimensional fluorescence parallel factor analysis (PARAFAC) indicated that humic-like substances were much more easily degraded by heat-activated PDS pretreatment than protein-like substances. These results indicated that some unsaturated NOM fractions were first degraded and then mineralized to carbon dioxide during pretreatment. Meanwhile, the destroyed structure of humic substances might hinder its binding with high valence cations to reduce the possibility of high valence cations deposited on the membrane surface, thereby reducing membrane fouling. Therefore, membrane fouling could be significantly mitigated due to the shifts of NOM concentration and structure by heat-activated PDS pretreatment in the surface water treatment. Graphical abstract: Image 1 Highlights: The heat-activated peroxydisulfate was adopted as a pretreatment prior to ultrafiltration. Suitable temperatures for mitigating membrane fouling by pre-oxidation were above 50 °C. Structural destruction and mineralization of natural organic matter occurred simultaneously in oxidation process. The destroyed structure of humic substances might hinder its binding with high valence cations.